Tamoxifen treatment adherence assessment by women with breast cancer - Rangel, Caroline Oliveira; Colet, Christiane de Fátima; Bandeira, Vanessa Adelina Casali; Gelatti, Gabriela Tassotti; Salazar, Rodrigo Fernando dos Santos; Horn, Roberta Cattaneo (Revista de Epidemiologia e Controle de Infecção, 2020)
Justification and objectives: oral antineoplastic therapy has advantages compared to othertherapies for the treatment of cancer, as it is administered at home, in a simple and fast way.However, this therapy increases patients’ responsibility for their treatment, and compliance iscritical to its effectiveness. Few studies are evident regarding pharmacotherapeutic follow-upin oral antineoplastic therapy. In this context, this study seeks to assess adherence to tamoxifentreatment in women with breast cancer, before and after pharmacotherapeutic follow-up.Methods: this is a randomized, quantitative clinical study. Data collection was carried out forsix months. Random randomization was divided into a control group and a follow-up group,with the follow-up subdivided into before and after follow-up. The follow-up group receivedindividual pharmaceutical interventions monthly. Adherence was assessed by The BriefMedication Questionnaire, Brazilian version and drug-related problems as to necessity,effectiveness, and safety. Results: after pharmaceutical follow-p, a difference was observedbetween the follow-up group and the control group regarding physical activity (p=0.043),treatment adherence (p=0.006), reduction of side effects (p=0.003) and associated diseases(p=0.002). The most frequent drug-related problems were safety and adherence, for which 54pharmaceutical interventions were performed. The side effects described by patients mainlyaffected the genital system and gastrointestinal tract. Conclusion: it was evident thatpharmacotherapeutic follow-up effectively contributed to adherence to treatment withtamoxifen and the pharmaceutical interventions performed contributed to prevention andreduction of drug-related problems.